Ecobrick: Building Basic Alternative Based On Eco-Friendly Methods Using Inorganic Waste In Punten Village - Susilowati, Susilowati - (Journal of Innovation and Applied Technology, 2023)
The purpose of this program is to introduce the community to how to sort and utilize the waste generated through the Ecobrick program: Alternative Building Bases in Punten Village Based on Environmentally Friendly Methods Using Inorganic Waste. This activity is carried out for 5 months from July to November 2022 The implementation method used in this program is data collection, preparation, program implementation includes socialization and training, monitoring and evaluation, and finally the preparation of reports. In addition, the activities that have been carried out include: Forum Group Discussion to village heads and related ranks, simulation and training activities targeted at the community, development of the construction of a waste bank in Punten Village, and activities ending with evaluation activities for the community.